Cumulative effects of titanium dioxide nanoparticles in UASB process during wastewater treatment. (1st January 2021) - Cervantes-Avilés, Pabel; Durán Vargas, J. Beatriz; Akizuki, Shinichi; Kodera, Toshimitsu; Ida, Junichi; Cuevas-Rodríguez, Germán
Abstract: Titanium dioxide nanoparticles (TiO2 NPs) are widely used in consumer products and one of their major fate is the wastewater treatment plants. However, NPs eventually arrive to aquatic and terrestrial ecosystems via treated water and biosolids, respectively. Since low concentration of NPs is accumulating in the upflow anaerobic sludge blanket (UASB) reactors that treat wastewater and reclaim water quality, the accumulation of TiO2 NPs in these reactors may impact in their performance. In this work, the long-term effects of TiO2 NPs on the main benefits of treating wastewater by UASB reactors such as, biogas production, methane fraction in biogas and organic matter removal were evaluated. Evaluation consisted of monitoring such parameters in two identical UASB reactors, one UASB-Control (without NPs) and the experimental one (UASB-TiO2 NPs) that received wastewater with TiO2 NPs. The fate of NPs in the UASB reactor was also determined. Results indicated that biogas production increased by 8.8% due to the chronic exposure of UASB reactor to TiO2 NPs during the first 44 days of experiment. However, the methane content in the biogas had no significant differences between both UASB, ranging between 78% and 90% of methane during the experiment. The removal of organic matter in both UASB was similar and ranged 92–98% along the experimental time. This means that accumulation of TiO2 NPs did not altered the biogas production and organic matter removal. However, the content of total volatile solids (TVS) in UASB-TiO2 NPs dropped off from 137.8 g to 64.2 g in 84 days, while for control reactor that decreased from 141.6 g to 92.4 g in the same period. Hence, the increased biogas production in the UASB exposed to TiO2 was attributed to hydrolysis of the TVS in this reactor. The main fate of TiO2 NPs was the granular sludge, which accumulated up to 8.56 mg Ti/g, which represent around 99% of the Ti spiked to the reactor and the possible cause of the biomass hydrolyzation in the UASB. Disposal of UASB sludge containing NPs from may raise ecotoxicological concerns due to the use of biosolids in agricultural activities. Graphical abstract: Image 1 Highlights: Student t-test p > 0.05 indicated the non-effect of TiO2 NPs on CODs removal by UASB. Biogas production increased in UASB reactor due to the chronic exposure of to TiO2 NPs. Methane content of biogas was 78–90% during long term exposure to TiO2 NPs. The fate of 99% of TiO2 NPs was the granular sludge of the UASB.